Systematic Review of COVID Spillover and Online Education Pedagogy - Aziz, Haroon; Malik, Samina; Ahad, Abdul; Javed, Umair (Journal of Education and Vocational Research, 2020)
This paper has touched one of the most critical area affected due to pandemic situation created by the COVID-19 and its powerful spillover effect on education sector by customizing education pedagogy. Earlier researchers have studied online education separately, whereas this paper discussed the natural transition and systematic review of upsurge of e-learning. The objective of this paper is to make the systematic review of COVID spillover and transition towards e-learning education pedagogy through theoretical framework. The study makes systematic review of switchover towards e-learning and spillover effect of COVID-19 and customization of the education pedagogy. In this study, past literature has been utilized to make critical analysis of spillover effect of COVID-19 and impact on education pedagogy by creation of prepositions. The findings of the study reveal that in the exceptional circumstances of COVID-19, e-learning transition has taken place from conventional to e-learning modules. All over the world, countries have shifted towards online education by schooling out but classes in campaign ignited by Chinese government. The same has also been replicated in other countries of the world during COVID-19.